Disruptive Innovation on Competition Law: Regulation Issues of Online Transportation in Indonesia - Fajar, Mukti; Mutiarin, Dyah; Setianingrum, Reni Budi (European Journal of Economics and Business Studies, 2019)
Disruptive innovation such as online transportation business is a leap of innovations of in services that triggered chaos in field of competition law. The emergence of new cumbent with its disruptive innovation has disturbed the market that dominated by the incumbent. This chaos cannot be overcome by the same legal approach because it has a different business model, in fact, it also happened in Indonesia. This study aims to: (a) reviewing whether disruptive innovation infringes the principles and provisions of competition law and; (b) identifying and evaluating various regulations regarding online transportation in Indonesia. The method of this research is normative legal research, which examines various legal principles, legal theories, and legislation. Findings of this study are; First, disruptive innovation is not an unlawful act because it does not infringe any provisions in the competition law. And also, this innovation is not contravene with the public order; its using new business platforms that are different from old business models. Second, Indonesian government has regulated this disruptive innovation by issuing regulation which has been sued for judicial review and amendment. Finally, Indonesian government has formulated an accommodative regulation format, i.e., online transportation is equalized to the specialized rental transportation.
Keywords: word: disruptive innovation, competition law, online transportation, regulation